UV-moisture-anaerobic heating triple-cured acrylic uv glue and preparation method thereof

CN122898243APending Publication Date: 2026-10-13YANTAI KAISHENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611033710.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

活性稀释剂 20~40%;

Benefits of technology

本发明创新性地将UV光固化、湿气固化和厌氧加热固化三种机理集成于单组分体系内,且三种固化方式并非简单叠加,而是通过促进剂等组分的调配实现了动力学上的协同加速。其中,UV固化实现秒级快速定位与表干,为后续固化提供初始强度;湿气固化不受光线限制,负责完成阴影区域及胶层深层的缓慢而彻底的固化;厌氧加热固化在隔绝氧气的粘接缝隙中,通过温和加热进一步激发深层交联,解决了现有单一及双重固化体系在复杂结构和阴影区域固化不完全的根本性缺陷,大幅拓宽了应用场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of acrylic adhesive, and discloses a UV-moisture-anaerobic heating triple-curing acrylic UV adhesive and a preparation method thereof, which is composed of the following components in percentage by weight: 30-55% of an acrylic ester prepolymer; 20-40% of an active diluent; 2-6% of a UV photoinitiating system; 3-8% of a moisture curing agent; 2-7% of an anaerobic curing system; 1-4% of an accelerator; 0.5-2% of an anti-yellowing agent; 0.3-1.5% of a stabilizer; 1-3% of an adhesion promoter; and 0.1-0.8% of a defoaming agent; wherein the acrylic ester prepolymer is a compounded system of aliphatic polyurethane acrylate and bisphenol A epoxy acrylate, and the weight ratio of the two is 1:0.8-1.2; and wherein the application effectively inhibits the self-polymerization reaction of active components in the system during storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of acrylic adhesives, specifically to a UV-moisture-anaerobic heating triple-curing acrylic UV adhesive and its preparation method. Background Technology

[0002] UV-curable acrylic adhesives are widely used in electronic component bonding, optical instrument assembly, and precision machinery fixing due to their advantages such as fast curing speed, solvent-free curing, and low energy consumption. However, the curing process of these adhesives is highly dependent on direct ultraviolet light irradiation, resulting in a fundamental limitation: curing will not stop when light cannot reach the target area. In bonding scenarios with complex three-dimensional structures, opaque or highly UV-absorbent substrates, incomplete curing or even failure to cure may occur in shaded areas because light cannot reach them directly, seriously affecting the reliability of the bond and the long-term service performance of the product.

[0003] To overcome the limitations of single UV curing, the industry has gradually developed dual-curing technologies, mainly including UV / moisture, UV / anaerobic, and UV / thermal curing systems. The UV / moisture dual-curing system utilizes UV light for rapid surface drying and relies on ambient moisture for post-curing in shaded areas. The process is relatively simple, but its secondary curing speed is highly dependent on ambient temperature and humidity. In low-humidity or dry environments, the curing cycle is significantly prolonged, and the dense surface layer formed during initial UV curing hinders moisture penetration into the deeper layers of the adhesive, further slowing down the curing rate. The UV / anaerobic dual-curing system combines the advantages of rapid UV curing and the high bonding strength of anaerobic adhesives to metal substrates, making it suitable for assembling metal parts. However, its application is limited to bonding substrates where at least one side is an active metal substrate; for inert metals or non-metallic substrates, an additional activator is usually required, resulting in poor versatility. The UV / thermal curing system requires additional heating equipment, has high energy consumption, and is not suitable for temperature-sensitive electronic components or substrates.

[0004] Furthermore, while some existing acrylic adhesives claim to offer multiple curing options, they generally suffer from poor synergy in the curing system, uneven curing rates, insufficient bond strength, and suboptimal environmental resistance in practical applications. Specifically: First, there is a contradiction between interfacial compatibility and reaction kinetics among multiple curing mechanisms, leading to mutual interference during curing and making it difficult to form a uniform, high-density interpenetrating polymer network, resulting in a bottleneck effect in the performance of the cured product. Second, curing efficiency and final bond performance are severely dependent on external conditions such as ambient temperature and humidity, substrate type, and oxygen concentration, lacking a universal and robust curing solution. Third, core indicators such as tensile shear strength, high and low temperature impact resistance, chemical resistance, and anti-yellowing properties of the cured adhesive layer often fail to simultaneously meet high-end application standards. Fourth, single-component systems designed to meet multiple curing activities exhibit a fundamental contradiction between long-term storage stability and rapid curing activity, a problem that existing technologies have failed to effectively resolve. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a UV-moisture-anaerobic heating triple-curing acrylic UV adhesive and its preparation method, which effectively inhibits the self-polymerization reaction of active components in the system during storage.

[0006] A UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, comprising the following components by weight percentage: Acrylic ester prepolymer 30~55%; Reactive diluent 20-40%; UV photoinitiating system 2~6%; Moisture curing agent 3~8%; Anaerobic solidification system 2~7%; Accelerator 1~4%; Anti-yellowing agent 0.5~2%; Stabilizer 0.3~1.5%; Adhesion promoter 1~3%; Defoamer 0.1~0.8%; The acrylate prepolymer is a compound system of aliphatic polyurethane acrylate and bisphenol A epoxy acrylate, with a compound weight ratio of 1:0.8~1.2.

[0007] Furthermore, the reactive diluent is a compound of a monofunctional reactive diluent and a polyfunctional reactive diluent, with a compounding weight ratio of 1:1.2~1.8; the monofunctional reactive diluent is isobornyl acrylate, and the polyfunctional reactive diluent is a compound of tricyclodecanediethanol diacrylate and tripropylene glycol diacrylate, with a compounding weight ratio of 1:0.9~1.1.

[0008] Furthermore, the UV photoinitiating system is a compound system of Norish type I photoinitiator and Norish type II photoinitiator, with a compound weight ratio of 1:0.7~1.3; the Norish type I photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the Norish type II photoinitiator is a compound of benzophenone and ethyl 4-dimethylaminobenzoate, with a compound weight ratio of 1:0.8~1.2.

[0009] Furthermore, the moisture curing agent is a product of a compound containing isocyanate groups modified with polyethylene glycol monomethyl ether. The compound containing isocyanate groups is a mixture of isophorone diisocyanate and toluene diisocyanate, and the modification ratio is compound containing isocyanate groups: polyethylene glycol monomethyl ether = 1:0.3~0.5.

[0010] Furthermore, the anaerobic curing system is a compound system of organic peroxide and anaerobic accelerator; the organic peroxide is benzoyl peroxide, and its amount accounts for 1 to 4% of the total weight of the system; the anaerobic accelerator is N,N-dimethylaniline, and its amount accounts for 1 to 3% of the total weight of the system.

[0011] Furthermore, the accelerator is a compound of triethanolamine and dibutyltin dilaurate, with a compound weight ratio of 1:1.0~1.4; the anti-yellowing agent is a compound of hindered amine light stabilizer and ultraviolet absorber, with a compound weight ratio of 1:0.8~1.2.

[0012] Furthermore, the stabilizer is hydroquinone monomethyl ether; the adhesion promoter is γ-methacryloyloxypropyltrimethoxysilane; and the defoamer is polydimethylsiloxane.

[0013] A method for preparing the aforementioned UV-moisture-anaerobic heating triple-curing acrylic UV adhesive includes the following steps: Step 1: Weigh the acrylate prepolymer and reactive diluent by weight percentage, add them to a reactor equipped with a stirrer and temperature control device, and stir and mix for 15 to 25 minutes at 25~35℃ and 200~300 r / min to obtain the basic mixture; Step 2: Add the UV photoinitiator, anti-yellowing agent, and stabilizer to the base mixture, maintain the temperature at 25~35℃ and the speed at 200~300r / min, and continue stirring for 20~30min; Step 3: Add moisture curing agent, anaerobic curing system and accelerator to the system in Step 2, adjust the speed to 350~450 r / min, and stir for 30~40 min; Step 4: Add adhesion promoter and defoamer to the system in step 3, adjust the speed to 250~350 r / min, and continue stirring for 10~15 min; Step 5: Filter the mixture obtained in Step 4 with a filtration accuracy of 0.22~0.45μm, and then degas for 15~20min under vacuum of -0.08~-0.10MPa and temperature of 25~35℃ to obtain the UV-moisture-anaerobic heating triple-curing acrylic UV adhesive.

[0014] A method for curing the UV-moisture-anaerobic heating triple-curing acrylic UV adhesive includes the following sequential synergistic curing steps: Irradiation was performed using UV lamps with wavelengths of 365~405nm, an irradiation intensity of 50~150mW / cm², and an irradiation time of 3~10s. Curing time is 2-8 hours at a temperature of 20-30℃ and a relative humidity of 30-80%. Heat at 40~80℃ for 10~30 minutes.

[0015] Compared with the prior art, the UV-moisture-anaerobic heating triple-curing acrylic UV adhesive and its preparation method provided by the present invention have the following significant advantages: This invention innovatively integrates three mechanisms—UV curing, moisture curing, and anaerobic heating curing—into a single-component system. These three curing methods are not simply superimposed; rather, synergistic acceleration is achieved through the formulation of accelerators and other components. Specifically, UV curing enables rapid positioning and surface drying within seconds, providing initial strength for subsequent curing; moisture curing, unrestricted by light, is responsible for the slow but thorough curing of shaded areas and deeper layers of the adhesive; and anaerobic heating curing, within oxygen-isolated adhesive gaps, further stimulates deep cross-linking through gentle heating. This invention overcomes the fundamental shortcomings of existing single and dual curing systems, which suffer from incomplete curing in complex structures and shaded areas, significantly expanding its application scenarios.

[0016] By optimizing a prepolymer system that combines aliphatic polyurethane acrylate and bisphenol A epoxy acrylate, and combining it with a specific ratio of reactive diluent and synergistic curing system, the cured adhesive layer forms a highly cross-linked interpenetrating polymer network with excellent mechanical properties. Tensile strength reaches over 35 MPa, shear strength over 18 MPa, and peel strength over 3.5 N / mm, while maintaining excellent flexibility and rigidity. Simultaneously, the combined use of hindered amine light stabilizer and UV absorber endows the adhesive layer with excellent anti-yellowing properties, maintaining high optical transparency even after prolonged UV irradiation. The adhesive layer exhibits stable performance over a wide temperature range of -40 to 120℃, demonstrating outstanding resistance to thermal shock, vibration, and various chemical corrosion, fully meeting the stringent requirements of high-end electronics, optics, and mechanical fields.

[0017] This invention provides a single-component adhesive that can be directly applied without on-site weighing and mixing. This avoids the curing defects caused by uneven mixing in two-component formulations from the outset, significantly simplifying the operation process and improving the consistency of industrial production efficiency. Simultaneously, by introducing precisely measured stabilizers, the self-polymerization reaction of the active components in the system is effectively suppressed during storage, allowing the adhesive to be stably stored for more than 6 months under sealed conditions at room temperature without significant performance degradation. This successfully balances the contradiction between high curing activity and long-term storage stability.

[0018] Moisture curing utilizes the inherent humidity of the environment, requiring no additional equipment investment. Anaerobic heating curing requires temperatures of only 40-80℃, far lower than traditional thermal curing processes, resulting in minimal thermal impact on the substrate, making it particularly suitable for components containing heat-sensitive elements. Furthermore, the introduction of silane coupling agents in the adhesive formulation enables excellent adhesion to various substrates such as metals, glass, plastics, and ceramics, eliminating the need for pre-coating activators. The entire system is 100% solids, free of volatile organic solvents, and operates without pollution or odor, meeting green and environmentally friendly production and usage requirements. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail and completely below with reference to specific embodiments and comparative examples. The following embodiments are for illustrative purposes only and should not be construed as limiting the invention.

[0020] In the following examples and comparative examples, all raw materials were of industrial grade or higher purity. Unless otherwise specified, the amounts of each component are expressed as weight percentages (wt%). The main equipment used for preparation and testing included: a stainless steel reactor (2L capacity, equipped with an anchor-type stirring paddle) with a mechanical stirring and temperature control jacket, a vacuum degassing machine, a precision electronic balance (accuracy 0.01g), 0.22μm and 0.45μm polytetrafluoroethylene (PTFE) filter membranes, a UV-LED irradiation device (wavelength switchable 365nm / 385nm / 405nm, adjustable light intensity, equipped with a UV-A radiometer), a constant temperature and humidity chamber (temperature control accuracy ±0.5℃, humidity control accuracy ±3%RH), and an electrically heated drying oven (temperature control accuracy ±1℃).

[0021] The performance tests were conducted according to the following national and industry standards: Tensile strength was tested according to GB / T 1040.2-2006, using dumbbell-shaped specimens at a tensile rate of 5 mm / min; Shear strength was tested according to GB / T 7124-2008, using stainless steel specimens (grade 304), stainless steel-aluminum specimens, or glass-stainless steel specimens as the substrate, with an overlap area of ​​25 mm × 12.5 mm and an adhesive layer thickness controlled at 0.2 ± 0.05 mm; Peel strength was tested according to GB / T 2791-1995, using a T-type peel method at a peel rate of 100 mm / min; Yellowing index (ΔYI) was tested according to ASTM standards. According to the E313 standard, a QUV ultraviolet aging test chamber was used. After continuous irradiation at a wavelength of 340nm and an intensity of 0.68W / m² for 1000 hours, the difference in yellow index before and after irradiation was measured using a spectrophotometer. The high and low temperature resistance performance was evaluated using a high and low temperature shock cycling test. Each cycle consisted of holding at -40℃ for 2 hours, then increasing the temperature to 120℃ at a rate of 5℃ / min and holding for 2 hours, followed by decreasing the temperature to -40℃ at a rate of 5℃ / min, for a total of 50 cycles. After the cycles, the adhesive layer was visually inspected for cracking or peeling. The adhesive was soaked or peeled, and the shear strength and peel strength retention rate were tested. Chemical resistance was assessed by immersing cured adhesive samples in analytical grade acetone, analytical grade anhydrous ethanol, and commercially available 10W-40 machine oil for 72 hours. After removal, the surface liquid was wiped dry with filter paper, and the appearance changes of the adhesive layer (swelling, softening, dissolution) were observed. Shear strength was tested after 2 hours under standard conditions, and the strength retention rate was calculated. Storage stability was assessed by sealing the adhesive in an aluminum tube and storing it at 25℃±2℃ in the dark for 6 months. The rotational viscosity change rate before and after storage was tested according to GB / T 2794-2013, and the shear strength of the cured adhesive layer after storage was also tested.

[0022] Example 1

[0023] A UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, based on a total weight of 1000g, has the following components and dosages: Table 1. Components and Dosage

[0024] The total weight percentage of each component is 100%, specifically: acrylate prepolymer 36% (aliphatic polyurethane acrylate 18% + bisphenol A epoxy acrylate 18%), reactive diluent 25% (IBOA 8% + TCDDMDA 9% + TPGDA 8%), UV photoinitiator system 4.0% (1173 1.8% + BP 1.2% + EDAB 1.0%), moisture curing agent 5.0%, anaerobic curing system 3.5% (BPO 2.0% + DMA 1.5%), accelerator 2.2% (triethanolamine 1.0%, dibutyltin dilaurate 1.2%), anti-yellowing agent 1.1% (HALS 0.6% + UV-P 0.5%), stabilizer 0.8%, adhesion promoter 2.0%, and defoamer 0.4%.

[0025] The preparation method of the adhesive in this embodiment is as follows: Preparation Step 1, Basic Mixing: Accurately weigh 180g of aliphatic polyurethane acrylate, 180g of bisphenol A epoxy acrylate, 80g of IBOA, 90g of TCDDMDA, and 80g of TPGDA using a precision electronic balance, and add them sequentially to a 2L stainless steel reactor (equipped with an anchor-type stirrer and a circulating water jacket temperature control device). Start stirring, set the speed to 250r / min, and turn on the jacket circulating water to control the temperature of the materials in the reactor at 30±1℃. Stir and mix for 20min. During the stirring process, the materials gradually change from an initial layered or slightly turbid state to a uniform, transparent, light yellow viscous liquid without visible particles, thus obtaining the basic mixture.

[0026] Preparation step 2: Adding the photoinitiator system and additives: Under the conditions of maintaining a temperature of 30±1℃ and a rotation speed of 250r / min, add the following components to the base mixture obtained in step 1 in the following order (each component is added approximately 30s apart to ensure gradual dispersion): 1173 18g, BP 12g, EDAB 10g, HALS 6g, UV-P 5g, MEHQ 8g. After the addition is complete, continue stirring for 25min. During the stirring process, observe the material; it gradually changes from the initial localized uneven color to a uniform light amber transparent liquid, with no visible particulate suspensions or precipitates, indicating that the photoinitiator and additives have been fully dissolved and dispersed.

[0027] Preparation step 3, adding to the curing system: Under the condition of maintaining a temperature of 30±1℃, add 50g of modified moisture curing agent, 20g of BPO (pre-wetted and ground into a slurry in 5g of IBOA for dispersion), 15g of DMA, 10g of triethanolamine, and 12g of dibutyltin dilaurate to the system obtained in step 2 in sequence. Increase the stirring speed to 400r / min and continue stirring for 35min. The purpose of increasing the stirring speed is to ensure that the BPO solid particles obtain sufficient shear dispersion force in the viscous system, while avoiding early gelation reactions that may be caused by excessively high local isocyanate concentrations. At the end of stirring, the mixture is a uniform, slightly yellow, transparent liquid without any sediment, layering, or visible suspended particles.

[0028] Preparation step 4: Add adhesion promoter and defoamer: Add 20g of KH-570 and 4g of polydimethylsiloxane to the system obtained in step 3, reduce the stirring speed to 300r / min (because the amount of these two components added is small and they are liquids, excessive shear force is not required), and continue stirring for 12min. At this time, there are no bubbles floating on the surface of the material, and no visible microbubbles are visible inside under transmitted light irradiation; the system is in a uniform and transparent state.

[0029] Preparation step 5, filtration and vacuum degassing: The mixture obtained in step 4 is poured into a pressure filtration device equipped with a 0.3μm PTFE filter membrane and filtered under nitrogen pressure of 0.2MPa to remove any small impurities and insoluble matter that may be present in the system. The filtrate is transferred to a vacuum degassing tank and degassed for 18 minutes under vacuum conditions of -0.09MPa (absolute pressure inside the tank is approximately 0.01MPa) and temperature of 30±1℃. In the first 3-5 minutes of degassing, small bubbles rise and burst on the surface of the material; as degassing continues, the number and rising rate of bubbles gradually decrease, until the surface of the material is completely calm after 18 minutes, with no bubbles emerging. The resulting product is the UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, which is a light amber-colored, uniform, transparent, bubble-free viscous liquid. The viscosity, measured by a rotational viscometer at 25℃, is 1850 mPa·s.

[0030] Preparation step 6, packaging and storage: Fill the adhesive obtained in step 5 into a pre-cleaned and dried aluminum tube, seal the opening of the aluminum tube with aluminum film heat seal, label it and store it in a cool and dry place (temperature ≤25℃, relative humidity ≤60%, away from light).

[0031] The curing method of the adhesive in this embodiment is as follows: (a) UV Curing: Apply the adhesive to the clean surface of a stainless steel test piece using a pneumatic dispensing machine in dots approximately 3 mm in diameter. Cover the test piece with another stainless steel test piece and gently press to spread the adhesive layer evenly, forming an overlap area of ​​25 mm × 12.5 mm. The adhesive layer thickness is controlled to be approximately 0.2 mm. Irradiate the test piece vertically from above with a 365 nm wavelength UV-LED lamp at a distance of 5 cm (from the lamp surface to the test piece surface). The measured light intensity on the test piece surface using a UV-A radiometer is 100 mW / cm², and the irradiation time is 5 seconds. After irradiation, the adhesive layer surface is dry and non-sticky to the touch, indicating that preliminary positioning and bonding strength has been established between the test pieces, allowing for safe subsequent transport and handling.

[0032] (b) Moisture Curing: Place the UV-cured adhesive test pieces on a sample rack inside a constant temperature and humidity chamber, ensuring that the adhesive layer between the test pieces is exposed to the circulating air inside the chamber. Set the temperature to 25±1℃ and the relative humidity to 50±3%, and let it stand for 4 hours. During this process, the modified isocyanate groups in the adhesive layer undergo a hydrolytic condensation reaction with water molecules in the ambient air, generating urea bond crosslinking points, allowing the adhesive layer to gradually cure in the shadow areas that UV light cannot reach and in the deeper parts of the adhesive layer.

[0033] (c) Anaerobic Heating Curing: After moisture curing, the bonded specimens were removed from the constant temperature and humidity chamber and immediately placed in an electric heating drying oven preheated to 60±1℃ for 20 minutes. During this process, the bonding gaps between the metal specimens were in a relatively oxygen-deficient state (due to the tight contact of the metal surfaces and the filling of the gaps by the adhesive layer, external air could not enter). At the same time, the trace iron ions on the surface of the stainless steel specimens catalyzed the decomposition of BPO. Under the promotion of DMA, BPO decomposed at 60℃ to produce benzoyl free radicals and benzene free radicals, which triggered further free radical polymerization and cross-linking reactions of the remaining acrylate double bonds, thereby increasing the final cross-linking density and bonding strength of the adhesive layer. After heating, the specimens were removed and placed under standard environmental conditions (23±2℃, relative humidity 50±5%) for 24 hours before various performance tests were conducted.

[0034] Example 2

[0035] A UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, based on a total weight of 1000g, has the following components and dosages: Table 2. Components and Dosage

[0036] The main difference between the formulation strategy in this embodiment and that in Example 1 is: (1) The total amount of prepolymer was reduced from 36% to 30% (both were 15%), and aliphatic polyurethane acrylate with a lower molecular weight was selected to reduce the viscosity of the system. (2) The total amount of reactive diluent remained unchanged at 25%, but the proportion of monofunctional IBOA was increased to further reduce the viscosity of the system and improve the leveling and penetration ability to fine gaps. (3) The amount of moisture curing agent was reduced from 5% to 3%, and the modification ratio was adjusted from 1:0.4 to 1:0.3, which slowed down the reaction rate of moisture curing and is suitable for scenarios where there is no high requirement for moisture curing speed. (4) The total amount of anaerobic curing system was reduced from 3.5% to 2.5% (BPO 1.5% + DMA 1.0%) to meet the anaerobic curing requirements at lower temperatures (50℃); (5) The total amount of UV photoinitiator system was reduced from 4.0% to 3.0%, which moderately reduced the concentration of photoinitiator and thus appropriately slowed down the starting speed of photocuring, which is conducive to having more operating time before light irradiation; (6) The dosage of anti-yellowing agent, stabilizer, accelerator, adhesion promoter and defoamer shall be appropriately reduced in proportion. The total amount of each component shall be 100%.

[0037] The preparation method, process steps, and operating parameters of this embodiment are basically the same as those of Example 1, with only the following adjustments: (1) The specific weighing values ​​of each component are replaced with the corresponding values ​​in Example 1 according to the dosage in the table above; (2) The stirring time in preparation step 3 is adjusted from 35 min to 30 min (because the dosage of moisture curing agent and anaerobic curing system is reduced, the required sufficient dispersion time can be appropriately shortened). The remaining temperature, rotation speed, and time parameters are exactly the same as those in Example 1. The finished product is a light yellow, uniform, transparent, viscous liquid with a rotational viscosity of 1520 mPa·s at 25°C.

[0038] The curing method of the adhesive in this embodiment is as follows: (a) UV Curing: The sample was vertically irradiated with a 385nm UV-LED lamp at a distance of 5cm. The measured light intensity on the sample surface using a UV-A radiometer was 80mW / cm², and the irradiation time was 8s. (b) Moisture Curing: The sample was left to stand for 6 hours under constant temperature and humidity conditions of 22±1℃ and 40±3% relative humidity. Since the amount of moisture curing agent used in this embodiment was reduced by 40% compared to Example 1, and the relative humidity of the test environment was also lower, the moisture curing time was appropriately extended to compensate for the decrease in curing rate and ensure sufficient curing of the shaded areas. (c) Anaerobic Heating Curing: The sample was heated for 25 minutes in an electric heating drying oven at 50±1℃. Since the total amount of BPO / DMA in the anaerobic curing system in this embodiment was reduced by approximately 29% compared to Example 1, the heating time was appropriately extended to compensate for the reduction in the total amount of free radicals generated. Simultaneously, the heating temperature of 50℃ was 10℃ lower than the 60℃ in Example 1, resulting in less thermal impact on temperature-sensitive substrates. After curing, the sample was placed under standard conditions for 24 hours before performance testing.

[0039] Example 3

[0040] A UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, based on a total weight of 1000g, has the following components and dosages: Table 3. Components and Dosage

[0041] This embodiment demonstrates a formulation strategy oriented towards high crosslinking density and high adhesive strength. The main differences from Example 1 are: (1) The total amount of prepolymer was increased from 36% to 40% (20% each), and aliphatic polyurethane acrylate with a higher molecular weight (molecular weight 2500) was selected to enhance the flexibility and bulk strength of the adhesive layer by utilizing its longer flexible chain segments; (2) The amount of multifunctional reactive diluents TCDDMDA and TPGDA was increased from 9% and 8% to 10% and 9% respectively to increase the crosslinking point density of the cured adhesive layer; (3) The total amount of UV photoinitiator system was increased from 4.0% to 4.5% to meet the higher requirements of photoinitiation efficiency for higher viscosity systems and the higher concentration requirements of BP / EDAB hydrogen abstraction initiator system at a wavelength of 405nm; (4) The amount of moisture curing agent was increased from 5% to 7%, and the modification ratio was adjusted from 1:0.4 to 1:0.5. Appropriate modification is beneficial to control the moisture curing rate in a high humidity environment; (5) The amount of anaerobic curing system was increased from 3.5% to 4.5% (BPO 2.5% + DMA). 2.0%), which aims to release more free radicals under heating conditions to achieve more thorough deep curing; (6) The dosage of accelerators, anti-yellowing agents, stabilizers and adhesion promoters is also moderately increased year-on-year to meet the higher requirements of the higher prepolymer content system for dispersion uniformity and storage stability.

[0042] The preparation method of this embodiment is consistent with that of Example 1, except that the following items are adjusted: (1) The specific weighing values ​​of each component are replaced according to the dosage in the table above; (2) The stirring time of preparation step 1 is extended from 20 min to 25 min. Due to the high content and large molecular weight of the prepolymer, the initial viscosity of the system is high, and a longer mixing time is required to achieve a uniform and transparent state; (3) The stirring time of preparation step 3 is extended from 35 min to 40 min. Due to the significant increase in the dosage of moisture curing agent and anaerobic curing system, a longer stirring time is required to ensure that BPO and modified isocyanate are fully dispersed and uniformly distributed in the high viscosity system. Other parameters such as temperature and rotation speed are consistent with those of Example 1. The finished product is a light amber, uniform and transparent viscous liquid with a rotational viscosity of 2380 mPa·s at 25°C.

[0043] The curing method of the adhesive in this embodiment is as follows: (a) UV curing: The sample was vertically irradiated with a 405nm UV-LED lamp at a distance of 5cm. The measured light intensity on the sample surface was 120mW / cm², and the irradiation time was 4s. (b) Moisture curing: The sample was left to stand for 3 hours under constant temperature and humidity conditions of 28±1℃ and 70±3% relative humidity. Because the amount of moisture curing agent used in this embodiment was increased by 40% compared to Example 1, and with the higher ambient temperature and humidity, moisture curing could be completed in a shorter time. (c) Anaerobic heating curing: The sample was heated for 15 minutes in an electric heating drying oven at 70±1℃. Because the amount of anaerobic curing system used was increased by 29% compared to Example 1, and the heating temperature was increased from 60℃ to 70℃, the half-life of BPO was significantly shortened at this temperature, and the rate of free radical generation was greatly increased. Therefore, a shorter time was sufficient to complete the deep curing. After curing, the sample was placed under standard conditions for 24 hours before performance testing.

[0044] Comparative Example 1 (Single UV-cured acrylic adhesive) Based on a total weight of 1000g (the actual formula was later normalized to 100%), the components and their amounts are as follows: Table 4. Components and Dosage

[0045] Comparative Example 1 was designed to reflect the curing performance of a typical conventional acrylic UV adhesive that relies solely on a single UV curing agent and does not contain moisture-curing or anaerobic-curing components, thus providing a clear contrast to a triple-curing system. The total amount of all components was approximately 94.2%, with the remaining 5.8% made up to 100% using IBOA. After thorough mixing, samples were taken for testing to ensure the overall proportions were normalized. Comparative Example 1 did not contain modified moisture-curing agents, BPO, DMA, triethanolamine, dibutyltin dilaurate, HALS, or UV-P.

[0046] Preparation method: 360g of aliphatic polyurethane acrylate, 250g of IBOA (including supplementary parts), and 250g of TPGDA were added to a reactor and stirred for 20min at 30±1℃ and 250r / min to obtain a basic mixture; 30g of 1173, 20g of BP, and 8g of MEHQ were added, and the mixture was stirred for 25min at 30±1℃ and 250r / min; 20g of KH-570 and 4g of polydimethylsiloxane were added, and the stirring speed was reduced to 300r / min for 12min; the mixture was then filtered under pressure through a 0.3μm PTFE filter membrane, and vacuum degassed for 18min at -0.09MPa and 30±1℃, and then filled into aluminum tubes and sealed.

[0047] Curing method: UV irradiation curing only. The sample was irradiated for 5 seconds with a 365nm UV-LED lamp at a distance of 5cm and a measured light intensity of 100mW / cm² on the surface. After irradiation, the adhesive layer was surface-dry and not sticky, but no further moisture curing or anaerobic heat curing was performed. The sample was left to stand under standard conditions for 24 hours before various tests were conducted.

[0048] Comparative Example 2 (UV-Moisture Dual-Cure Acrylic Adhesive) Based on a total weight of 1000g (the actual formula was later normalized to 100%), the components and their amounts are as follows: Table 5. Components and Dosage

[0049] Comparative Example 2 was designed to reflect the performance level of the UV-moisture dual-curing system (excluding anaerobic heat-curing components). BPO, DMA, dibutyltin dilaurate, HALS, and UV-P were not added to the formulation. The total amount of all components was approximately 67.0%, with the remaining 33.0% made up to 100% with IBOA. After thorough mixing, samples were taken for testing.

[0050] Preparation method: 200g of aliphatic polyurethane acrylate, 100g of bisphenol A epoxy acrylate, IBOA (calculated as 12% + supplemented to 33.0%), and 100g of TPGDA were added to a reactor and stirred for 20min at 30±1℃ and 250r / min to obtain a basic mixture; 20g of 1173, 15g of BP, 10g of EDAB, and 8g of MEHQ were added, and the mixture was stirred for 25min at 30±1℃ and 250r / min; 60g of modified moisture curing agent and 12g of triethanolamine were added, and the mixture was stirred for 35min at 400r / min; 20g of KH-570 and 5g of polydimethylsiloxane were added, and the mixture was stirred for 12min at 300r / min; the mixture was then filtered under pressure through a 0.3μm PTFE filter membrane, and vacuum degassed for 18min at -0.09MPa and 30±1℃, and then filled into aluminum tubes and sealed.

[0051] Curing method: A two-step process of UV irradiation and moisture curing was adopted. UV curing conditions were: wavelength 365nm, measured light intensity on the sample surface 100mW / cm², irradiation time 5s; moisture curing conditions were: temperature 25±1℃, relative humidity 60±3%, and standing time 72h (due to the lack of anaerobic heating curing to enhance crosslinking density, the moisture curing time was appropriately extended to ensure complete curing). After curing, the sample was placed under standard conditions for 24h before testing.

[0052] Performance Tests and Results: For the adhesives prepared in each embodiment and comparative example, the mechanical properties, aging resistance, chemical resistance, and storage stability of the cured adhesive layer were systematically tested according to the test standards and conditions described above. The advantages of the triple-curing system in terms of curing integrity were qualitatively verified using a shaded area curing simulation experiment. All tests were conducted under standard environmental conditions (23±2℃, relative humidity 50±5%), and each set of data represents the arithmetic mean of no fewer than five samples. The results are described below.

[0053] Table 6 Mechanical Properties

[0054] The mechanical property test results show that the tensile strength of Examples 1-3 is no less than 31 MPa, the shear strength (stainless steel / stainless steel) is no less than 17 MPa, and the peel strength is no less than 3.2 N / mm. All indicators are significantly better than those of Comparative Examples 1 and 2. Example 3, due to the use of a higher content of prepolymer (40%) and a combination of high-functionality reactive diluents (TCDDMDA 10% + TPGDA 9%), and a higher amount of anaerobic curing system (4.5%), forms the densest cross-linked network in the cured adhesive layer, achieving the optimal level of mechanical properties: tensile strength 42.6 MPa, stainless steel shear strength 24.5 MPa, and T-peel strength 5.1 N / mm. Comparative Example 1 (single UV curing) only has free radical cross-linking initiated by UV, without the supplementary cross-linking contribution of moisture and anaerobic curing. The cross-linking density of the adhesive layer is seriously insufficient, with a tensile strength of only 49% and a shear strength of only 41% of Example 1. Comparative Example 2 (UV-moisture dual curing) has better mechanical properties than Comparative Example 1 because it introduces urea bond crosslinking points generated by moisture curing. However, due to the lack of further crosslinking enhancement by anaerobic heating curing, its tensile strength (24.3 MPa) is only 64% of that of Example 1, and its shear strength (13.1 MPa) is only 60% of that of Example 1. The gap with the triple curing system is still significant.

[0055] Table 7 Aging resistance

[0056] The aging resistance test results showed that the yellowing index ΔYI of the three examples was controlled below 1.2. Among them, Example 2, due to the lowest amount of anti-yellowing agent (only 0.8%), obtained the lowest ΔYI value (0.88). This indicates that when the amount of UV photoinitiator system was also low (3.0%) and 385nm wavelength was selected for curing, the amount of initiator residue and photo-oxidation byproducts was low, and the system itself had a lower tendency to yellow. Comparative Examples 1 and 2, which did not add any anti-yellowing agent, had ΔYI values ​​as high as 3.56 and 4.12 after 1000h UV irradiation, respectively. The color of the adhesive layer visibly changed from the initial light yellow / colorless to a significant dark yellow or brownish-yellow. The ΔYI of Comparative Example 2 (4.12) was higher than that of Comparative Example 1 (3.56). This is because the aromatic isocyanate groups (from TDI) remaining in the modified moisture curing agent are more likely to undergo photo-rearrangement and quinone chromophore formation under UV irradiation, resulting in more severe yellowing. In 50 high and low temperature cycles ranging from -40℃ to 120℃, none of the three examples exhibited any cracking, blistering, or peeling, with shear strength retention rates ranging from 85% to 93%. In contrast, both comparative examples showed varying degrees of defects: Comparative Example 1 showed slight edge cracking (retention rate of only 61%), and Comparative Example 2 showed localized blistering and slight peeling (retention rate of 72%). The IPN structure with higher crosslinking density formed by the triple-curing system has richer stress relaxation and energy dissipation pathways in its network segments when facing the stress difference caused by drastic temperature changes, thus exhibiting significantly better thermal shock resistance than single-curing and dual-curing systems.

[0057] Table 8 Chemical Resistance

[0058] Chemical resistance test results showed that after 72 hours of immersion in acetone, anhydrous ethanol, and engine oil, the appearance of the adhesive layers in all three examples showed no visible changes, and the shear strength retention rate was above 81% (as high as 93%~97% in engine oil), demonstrating excellent chemical resistance. The cross-linked network structure of the single UV-cured adhesive layer in Comparative Example 1 was relatively loose. Solvent molecules penetrated into the gaps between the cross-linking points, causing significant swelling (only 28% strength retention rate in acetone) or softening (52% retention rate in ethanol). Comparative Example 2, due to the urea bond cross-linking introduced by moisture curing, increased the network density to some extent, resulting in better solvent resistance than Comparative Example 1 (46% retention rate in acetone), but still significantly inferior to the examples. This is because anaerobic heating curing, through a free radical mechanism, embedded new carbon-carbon cross-linking points on the network formed by UV and moisture curing, forming a denser and more chemically inert interpenetrating network structure, effectively blocking the penetration path of solvent molecules.

[0059] Table 9 Storage Stability

[0060] Storage stability test results showed that after 6 months of sealed and light-protected storage at 25°C, the viscosity change rate of all three examples was controlled within 6% (+3.8%, +4.6%, and +5.5%, respectively), and the shear strength after curing showed no significant decrease (Example 1 decreased from 21.8 MPa to 20.9 MPa, a decrease of only 4.1%), demonstrating good long-term storage stability. The viscosity change rate of Example 3 (+5.5%) was slightly higher than that of Examples 1 and 2, mainly because its higher prepolymer content and the presence of anaerobic curing components (BPO / DMA) made the system more prone to undergoing trace self-polymerization reactions during long-term storage at room temperature than the low-dosage formulations. However, with sufficient suppression by 1.2% MEHQ, it was still controlled within an acceptable range. Comparative Example 1 showed a sharp increase in viscosity (+19.7%) after 6 months, with visible localized gel particles and a significant decrease in fluidity. The shear strength after curing dropped sharply from the initial 8.9 MPa to 6.1 MPa (a decrease of 31.5%), indicating that the acrylate groups in the system exhibited a more concentrated and prominent self-polymerization tendency in the absence of the dispersion and dilution effect of moisture and anaerobic curing active components. In Comparative Example 2, the isocyanate groups of the moisture curing agent reacted slowly with trace amounts of moisture in the system during long-term storage, resulting in localized thickening and uneven pre-crosslinking (viscosity increase of +16.1%), and a decrease in performance after curing (shear strength decrease of 18.3%). The data from the three examples fully demonstrate the significant advantage of the triple-curing system in terms of storage stability compared to traditional single-curing and dual-curing acrylic adhesives.

[0061] Curing integrity of shaded areas: To visually verify the curing ability of the triple curing system of this invention in shaded areas, the following simulation experiment was designed: Two 304 stainless steel plates (100mm × 25mm × 2mm) were taken, and a rectangular groove with a width of 5mm, a depth of 1.5mm, and a length of 80mm was machined along the length direction on the base plate. Adhesive was evenly injected along the bottom of the groove (filling the groove), and the top plate was covered. A uniform pressure of 0.1MPa was applied using a clamp, ensuring the adhesive layer completely filled the groove and formed an adhesive layer approximately 0.2mm thick between the plates. In this structure, the adhesive layer at the bottom of the groove was completely blocked by the upper metal plate, preventing UV light from penetrating the stainless steel plate to reach the bottom of the groove. Each embodiment and comparative example was cured according to its respective specified curing scheme. After curing, the clamp was removed, and the lap shear strength of the specimen was tested on a universal testing machine. The specimen was then disassembled to observe the curing condition of the adhesive layer at the bottom of the groove. The results are as follows: Table 10 Curing Integrity Results of Shaded Areas

[0062] The results of the curing experiment in the shaded area clearly demonstrate the unique technical advantages of the triple curing system of this invention. In Comparative Example 1 (single UV curing), the adhesive layer at the bottom of the trench remained liquid and uncured because it could not receive UV irradiation at all. Only the adhesive layer at the edge of the trench and the UV-accessible area on the upper surface was cured, and the overlap shear strength was only 2.1 MPa. In Comparative Example 2 (UV-moisture dual curing), the adhesive layer at the bottom of the trench was cured to a certain extent through moisture curing, and the overlap strength reached 10.5 MPa. However, due to the lack of secondary crosslinking through anaerobic heating curing and the obstruction of moisture penetration by the metal interface, the degree of curing and hardness of the bottom area were still not as good as the surface area. In all three embodiments, the adhesive layer at the bottom of the trench was completely cured and had uniform hardness. The difference between the trench overlap shear strength (15.6~22.3MPa) and the planar overlap shear strength (17.2~24.5MPa) was much smaller than that in the comparative example. This fully demonstrates that the triple curing system, which combines UV rapid surface drying positioning, moisture penetration into the shadow area reaction, and anaerobic free radical supplementary crosslinking in the oxygen-deficient environment of metal gaps, can effectively solve the problem of incomplete curing in areas where light cannot reach.

[0063] Experimental conclusions Based on the system tests and comparative analyses of Examples 1-3 and Comparative Examples 1-2 above, the following experimental conclusions are drawn: The UV-moisture-anaerobic heating triple-curing acrylic UV adhesives of Examples 1-3 of this invention significantly outperform Comparative Example 1 (single UV curing) and Comparative Example 2 (UV-moisture dual curing) in all core performance indicators such as tensile strength, shear strength, peel strength, UV aging and yellowing resistance, high and low temperature cycle impact resistance, chemical corrosion resistance and storage stability of the cured adhesive layer. The underlying physical mechanism behind this performance leap lies in the following: UV curing rapidly cross-links the adhesive surface layer within seconds, providing initial bonding strength and positioning function; moisture curing utilizes the urea bond cross-linking points generated during the hydrolysis and condensation of water molecules and modified isocyanate groups in the environment to gradually cure the shadow areas inaccessible to UV light and the deeper parts of the adhesive layer; anaerobic heat curing, under the combined action of the natural oxygen-deficient environment of the metal bonding gap and mild heating (40~80℃), generates highly active benzoyl and benzene free radicals through the thermal decomposition of the BPO-DMA system, initiating additional free radical polymerization cross-linking of the remaining acrylate double bonds. This embeds new carbon-carbon covalent cross-linking bridges between the UV free radical cross-linking network and the moisture condensation cross-linking network, forming a highly interpenetrating composite cross-linking network structure (IPN) with maximized cross-linking density. This triple cross-linking network is inherently superior to any single cross-linking mechanism or a simple superposition of two cross-linking mechanisms.

[0064] The tensile strength, shear strength, and peel strength of Examples 1-3 have all met or exceeded the common requirements for the mechanical properties of adhesives in precision bonding of electronic components, fixation of optical devices, and assembly of metal structures, with tensile strength ≥31MPa, stainless steel shear strength ≥17MPa, and T-peel strength ≥3.2N / mm. Example 3, through a comprehensive strategy of increasing prepolymer content, selecting high molecular weight prepolymers, increasing the proportion of multifunctional reactive diluents, and increasing the anaerobic curing component, achieved outstanding levels of tensile strength (42.6MPa) and stainless steel shear strength (24.5MPa), representing a high-strength formulation direction for this system. Although Example 2 has relatively mild mechanical properties (tensile strength 31.5MPa), its low viscosity (1520mPa·s) gives it a unique advantage in scenarios with high requirements for adhesive rheological properties, such as capillary penetration bonding and filling of fine gaps. Example 1, with its balanced overall performance and moderate viscosity (1850mPa·s), constitutes the general recommended formulation of the adhesive of this invention.

[0065] Through the synergistic compounding of HALS and UV-P, the ΔYI of all three embodiments was controlled below 1.2 (far lower than the typical ΔYI range of 3-5 for conventional acrylic UV adhesives), meeting the stringent requirements for long-term maintenance of adhesive layer transparency in optical-grade bonding applications. Simultaneously, the triple-crosslinked IPN structure exhibited excellent mechanical retention (85%-93% strength retention) under extreme temperature cycling from -40°C to 120°C, and the degradation of mechanical properties under long-term UV irradiation was also far lower than that of the comparative system, confirming the reliability of this adhesive for long-term service in outdoor and harsh environments.

[0066] After 6 months of storage at 25°C in a light-proof and sealed environment, the viscosity change rate of all three examples was controlled within +6%, and the curing performance showed virtually no degradation, meeting the conventional storage period requirements (≥6 months) for industrial adhesive products. The ready-to-use characteristic of the single-component formulation avoids the on-site mixing process and curing defects caused by uneven mixing in traditional two-component triple-curing adhesives. At the same time, the reactivity of each reactive component in the formulation is precisely controlled under storage conditions (isocyanate is modified with polyethylene glycol monomethyl ether to reduce reactivity, BPO / DMA is in a stable state under aerobic conditions at room temperature, and the self-polymerization of acrylate groups is effectively suppressed by MEHQ), achieving an ideal balance between stability during storage and rapid curing during use.

[0067] By comparing the formulation differences and corresponding performance characteristics of the three embodiments, it is clear that the formulation system of the present invention provides users with a wide range of on-demand adjustment options: flexibility and rigidity can be balanced by adjusting the ratio of aliphatic polyurethane acrylate to bisphenol A epoxy acrylate; viscosity and crosslinking density can be controlled by adjusting the ratio of monofunctional and polyfunctional reactive diluents; different curing speeds, curing depths, and final performance requirements can be adapted by adjusting the amount of the three curing systems added; and different weather resistance and substrates can be adapted by adjusting the amount of anti-yellowing agent and adhesion promoter. This endows the adhesive of the present invention with universality and flexibility in a wide range of industrial fields, such as electronic component packaging, optical lens bonding and fixing, precision metal component assembly, and medical device assembly.

[0068] In this invention's triple curing scheme, UV curing requires only 3-10 seconds of irradiation, moisture curing utilizes naturally occurring moisture in the environment, and anaerobic heating curing takes place at only 40-80°C. None of the three curing methods require extreme conditions or complex and expensive specialized equipment. UV-LED lamps are already a standard configuration in the industry, and constant temperature and humidity chambers or natural indoor conditions can meet the requirements for moisture curing. Heating at 40-80°C can be easily achieved in industrial drying tunnels or ovens. In summary, this adhesive has a low barrier to industrialization and is highly compatible with existing electronic product assembly lines and optical component assembly processes.

[0069] The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive of this invention, in the form of a single-component formulation, organically integrates the three mechanisms of UV curing, moisture curing, and anaerobic heating curing into a single adhesive system. This fundamentally overcomes the inherent bottlenecks of traditional UV adhesives, such as the inability to achieve curing beyond the reach of light and the lack of continuous curing. Simultaneously, it solves multiple technical problems in existing dual-curing systems, including insufficient synergy, difficulty in simultaneously achieving mechanical and environmental resistance properties, and the challenge of balancing storage stability and curing activity. System test data from three embodiments and comparative analysis of comparative examples fully demonstrate the broad application prospects and significant technical and economic value of this invention in high-end manufacturing fields such as electronics, optics, and machinery.

Claims

1. A UV-moisture-anaerobic heating triple-curing acrylic UV adhesive, characterized in that, By weight percentage, it consists of the following components: Acrylic ester prepolymer 30~55%; Reactive diluent 20-40%; UV photoinitiator system 2~6%; Moisture curing agent 3~8%; Anaerobic solidification system 2~7%; Accelerator 1~4%; Anti-yellowing agent 0.5~2%; Stabilizer 0.3~1.5%; Adhesion promoter 1~3%; Defoamer 0.1~0.8%; The acrylate prepolymer is a compound system of aliphatic polyurethane acrylate and bisphenol A epoxy acrylate, with a compound weight ratio of 1:0.8~1.

2.

2. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The reactive diluent is a compound of monofunctional and polyfunctional reactive diluents with a compounding weight ratio of 1:1.2 to 1.8; the monofunctional reactive diluent is isobornyl acrylate, and the polyfunctional reactive diluent is a compound of tricyclodecanediethanol diacrylate and tripropylene glycol diacrylate with a compounding weight ratio of 1:0.9 to 1.

1.

3. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The UV photoinitiating system is a compound system of Norish type I photoinitiator and Norish type II photoinitiator, with a compound weight ratio of 1:0.7~1.3; the Norish type I photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone, and the Norish type II photoinitiator is a compound of benzophenone and ethyl 4-dimethylaminobenzoate, with a compound weight ratio of 1:0.8~1.

2.

4. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The moisture curing agent is a product of a compound containing isocyanate groups modified with polyethylene glycol monomethyl ether. The compound containing isocyanate groups is a mixture of isophorone diisocyanate and toluene diisocyanate, and the modification ratio is compound containing isocyanate groups: polyethylene glycol monomethyl ether = 1:0.3~0.

5.

5. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The anaerobic curing system is a compound system of organic peroxide and anaerobic accelerator; the organic peroxide is benzoyl peroxide, which accounts for 1 to 4% of the total weight of the system; the anaerobic accelerator is N,N-dimethylaniline, which accounts for 1 to 3% of the total weight of the system.

6. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The accelerator is a compound of triethanolamine and dibutyltin dilaurate, with a compound weight ratio of 1:1.0~1.4; the anti-yellowing agent is a compound of hindered amine light stabilizer and ultraviolet absorber, with a compound weight ratio of 1:0.8~1.

2.

7. The UV-moisture-anaerobic heating triple-curing acrylic UV adhesive according to claim 1, characterized in that, The stabilizer is hydroquinone monomethyl ether; the adhesion promoter is γ-methacryloyloxypropyltrimethoxysilane; and the defoamer is polydimethylsiloxane.

8. A method for preparing a UV-moisture-anaerobic heating triple-curing acrylic UV adhesive as described in any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Weigh the acrylate prepolymer and reactive diluent by weight percentage, add them to a reactor equipped with a stirrer and temperature control device, and stir and mix for 15 to 25 minutes at 25~35℃ and 200~300 r / min to obtain the basic mixture; Step 2: Add the UV photoinitiator, anti-yellowing agent, and stabilizer to the base mixture, maintain the temperature at 25~35℃ and the speed at 200~300r / min, and continue stirring for 20~30min; Step 3: Add moisture curing agent, anaerobic curing system and accelerator to the system in Step 2, adjust the speed to 350~450 r / min, and stir for 30~40 min; Step 4: Add adhesion promoter and defoamer to the system in step 3, adjust the speed to 250~350 r / min, and continue stirring for 10~15 min; Step 5: Filter the mixture obtained in Step 4 with a filtration accuracy of 0.22~0.45μm, and then degas for 15~20min under vacuum of -0.08~-0.10MPa and temperature of 25~35℃ to obtain the UV-moisture-anaerobic heating triple-curing acrylic UV adhesive.

9. A curing method for a UV-moisture-anaerobic heating triple-curing acrylic UV adhesive as described in any one of claims 1-7, characterized in that, The following co-curing steps are performed sequentially: Irradiation was performed using UV lamps with wavelengths of 365~405nm, an irradiation intensity of 50~150mW / cm², and an irradiation time of 3~10s. Curing time is 2-8 hours at a temperature of 20-30℃ and a relative humidity of 30-80%. Heat at 40~80℃ for 10~30 minutes.